Organized violence as a never-ending story? Reflections in light of the Russian aggression against Ukraine - Pries, Ludger (Frontiers in Sociology, 2022)
During the last decade, especially with the Russian aggression against Ukraine, armed conflicts and other forms of organized violence increased in volume and public discourse. In Sociology, violence and particularly organized violence were marginalized topics for a long time, not least because many sociologists considered violence as relic of traditional societies. Based on an analysis of major sociological studies and an empirical analysis of violence related mass data, we argue that (1) violence and organized violence are not vanishing, but genuine components of human coexistence, (2) especially in Europe we experienced (or at least perceived) some seven decades of living in social spaces without high levels of violence, (3) other world regions are violence-intensive social spaces for generations, and (4) in light of the aggression of Russian troops against Ukraine and further challenges to come, Sociology should intensify theoretical and empirical efforts in this field of research. We first sketch out some recent trends of organized violence and related social science debates, then summarize important sociological concepts of violence and organized violence, propose to differentiate between not violence-intensive social spaces (NoViSS) and violence-intensive social spaces (ViSS) and exemplify this distinction by some global data, and finally draw some conclusions for further research on organized violence in selected fields like forced migration.